Uncovering Impacts of Tourism on Social–Ecological Vulnerability Using Geospatial Analysis and Big Earth Data: A Karst Ethnic Village Perspective - Yiqin Bao; Hua Zhang; Chong Wu (Land)
The ethnic villages in karst regions, where the ecosystem and social systems are intricately linked, face the dual challenges of poverty and ecological sustainability. Tourism, as an emerging strategy adopted for poverty alleviation, has inevitably posed complex impacts on social–ecological systems (SES). However, due to the particularity of the SES in this region, the mechanisms through which tourism influences social–ecological systems remain unclear, hindering the achievement of eco-friendly economic growth. In this study, we first applied the vulnerability spectrum diagram (VSD) model assessment framework to various remotely sensed and socially sensed data to evaluate ecological and social vulnerability, taking Leishan County, a typical karst region in Guizhou, southwest China as a case study. Then, advanced geospatial analysis methods were adopted to investigate the spatial characteristics of the vulnerability index. Finally, we utilized the geographical detector to identify influencing factors and investigated their synergistic effects. Our results reveal that, within the studied area, social vulnerability is generally lower in the north than the south, while ecological vulnerability shows the other way around. Social vulnerability is significantly influenced by several tourism-related factors, such as transportation convenience and the preservation of traditional dwellings. These factors collectively exert a pronounced effect on social vulnerability mitigation. Moreover, ecological vulnerability, with the exception of rocky desertification, shows significant co-directional changes with social vulnerability, reflecting the fact that tourism factors indirectly shape the ecosystem. The development of ethnic village tourism in villages with better socio-economic conditions tends to effectively improve the quality of the ecological environment, whereas those with poorer conditions tend to exacerbate ecological damage. The findings drawn from this study convey important practical implications that assist in identifying key vulnerable areas in karst ethnic villages and support their sustainable development goals.